‘Something’s Brewing’: The Changing Trends in Alcohol Coverage in Australian Newspapers 2000–2011 - Azar, D.; White, S.; Bland, S.; Livingston, M.; Room, R.; Chikritzhs, Tanya; Durkin, S.; Gilmore, William; Wakefield, M. (Medical Council on Alcohol and Oxford University Press, 2014)
Aims: The portrayal of alcohol in the news media, including newspapers, plays an important role in influencing societal norms and setting public agendas. We present the first large-scale examination of news coverage of alcohol-related issues in Australian newspapers. Method: Content analysis was performed on a sample of alcohol-related newspaper articles (n = 4217) published across Australia from 2000 to 2011. Articles were coded for type, theme, prominence, topic slant, opinion slant and sources/spokesperson. Results: Across the period, the most common themes were promotion (21%), drink-driving (16%) and restrictions/policy (16%).Themes of restrictions/policy and responsible beverage services became more common over time. Promotion and business-related articles significantly declined over time. Overall, the topic slant of the majority of news related articles disapproved of alcohol use. Disapproval increased over time while approval of alcohol use decreased. While the slant of opinion pieces was predominantly approving of alcohol, this decreased over time. Presence of an alcohol industry representative in articles declined over time. Conclusion: The presentation of alcohol use in Australian newspapers became more disapproving over time, which may suggest that harmful alcohol use has become less acceptable among the broader Australian community.